(untitled) (Scientific journal of the Fergana State University, 2024)
By studying the theoretical and practical foundations of the preparatory group in teaching children to swim, we presented the materials of a pedagogical experiment that allow us to objectively assess the correctness of the proposed hypothesis and determine the possibility of its use. We showed 13-14-year-old swimmers how to develop speed.